Budaya On dan Giri pada Tokoh Sen dan Chihiro dalam Anime Spirited Away Karya Hayou Miyazaki - Dhea Lania; Umi Handayani (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
Anime is well known as a typical Japanese animation created with moving images that resemble human beings. Anime has a certain appeal as entertainment that entertains audiences. From another angle, however, anime also provides the moral and cultural messages that its creators wish to convey through each character's story and characterization. "Spirited Away" is an anime produced by Ghibli Studios, directed by Hayao Miyazaki. The animation "Spirited Away" depicts the struggles of a 10-year-old girl who works as a waitress at a hot spring in the spirit world. In the story, Spirited Away is the protagonist featured by the creator, who brilliantly plays the role of freeing her parents from the witch's spell that transformed them into pigs. The story is based On the cultural values and characterization demonstrated by Hayao Miyazaki in the anime. The purpose of this study is to find the "A (On) and (Giri)" culture in the characters of Spirited Away. The method used in this study is a descriptive qualitative method. Descriptive research attempts to gather informatiOn to describe a state, event, or phenomenOn in a specific and sequential manner. Using this method, conclusions can be drawn from the analysis conducted.